Effective Mechanical Responses of a Class of 2D Chiral Materials. Issue 10 (18th August 2020) - Wang, Yun-Che; Ko, Tsai-Wen; Ren, Xuejun
Abstract : Chiral materials may exhibit negative Poisson's ratio and deformation‐mode coupling phenomena. The finite element numerical method is adopted to analyze a class of 2D chiral and nonchiral materials and to show the effects of microstructural geometry on their effective elastic properties and coupling between tension/compression and bending. With the same area fraction (AF), nonchiral samples show larger effective moduli than chiral ones. The number of unit cells may reduce negativity in effective Poisson's ratio of the chiral samples due to nonuniform lateral deformation under uniaxial straining. Increasing AF in a hierarchical pattern in the chiral samples makes their Poisson's ratio more negative. Bending occurs in the chiral samples when they are under uniform, uniaxial, tensile, or compressive straining due to the coupling of deformation modes. The sensibility of tension–bending coupling may be controlled by the chiral microstructure. Optimization of the coupling sensitivity may help develop novel mechanical sensors. Abstract : Two‐dimensional doubly chiral material, fixed on the left edge, shows deformation‐mode coupling between horizontal tension and downward bending when under uniform straining on the right edge. Stress distributions are heterogeneous, and large Mises stresses occur in sigmoidal‐shape linking ligaments, as well as near the joints between the ligaments and circular units. The color bar is in units of Pascal.